Implications of the new WHO guidelines on HIV and infant feeding for child survival in South Africa - Tanya Doherty; David Sanders; Ameena Goga; Debra Jackson
The World Health Organization released revised principles and recommendations for HIV and infant feeding in November 2009. The recommendations are based on programmatic evidence and research studies that have accumulated over the past few years within African countries. This document urges national or subnational health authorities to decide whether health services should mainly counsel and support HIV-infected mothers to breastfeed and receive antiretroviral interventions, or to avoid all breastfeeding, based on estimations of which strategy is likely to give infants in those communities the greatest chance of HIV-free survival. South Africa has recently revised its clinical guidelines for prevention of mother-to-child HIV transmission, adopting many of the recommendations in the November 2009 World Health Organization's rapid advice on use of antiretroviral drugs for treating pregnant women and preventing HIV infection in infants. However, one aspect of the new South African guidelines gives cause for concern: the continued provision of free formula milk to HIV-infected women through public health facilities. This paper presents the latest evidence regarding mortality and morbidity associated with feeding practices in the context of HIV and suggests a modification of current policy to prioritize child survival for all South African children.